تراجم " صحيح البخاري " بين ابن رشد وابن ابن جماعة - دراسة مقارنة - دودي, شيماء (University of Eloued جامعة الجزائر, 2020)
"لقد اعتنى الأئمة –رحمهم الله تعالى- ""بالجامع الصحيح"" عناية فائقة، وتنوعت هممهم في شرحه وإيضاح مقاصده، ومما اعتنوا به تراجم أبوابه. ولم يحظ كتاب من كتب السنة بالخدمة والعناية مثلما حظي به ""صحيح البخاري""، وكان من أبرز العلماء الذين اهتموا بشرح تراجمه الإمام ابن رشيد السبتي، فألف فيه كتابا سماه "" ترجمان التراجم على أبواب صحيح البخاري""، والإمام بدر الدين ابن جماعة في كتابه الموسوم ب:"" مناسبات تراجم البخاري""، فكان تأليفهما في إبداء المناسبات لتراجم ""صحيح البخاري""، وبيان مدى مطابقة الأحاديث للترجمة، وقد حاولت هذه الدراسة تقديم مقارنة مختصرة بين الكتابين، وبيان أبرز نقاط الاتفاق والاختلاف بين الإمامين في شرح وتوجيه تراجم ""صحيح البخاري "The Imams, God bless them, took care of the ""right mosque"", and their importance in explaining it and clarifying its purposes, and what they were caring for, is the harmony of its doors. The book of Sunnites was not well served and cared for as it was received by ""true Bukhari"", and was one of the most prominent scholars who were interested in explaining his heritage, Imam Rashid Al-Sebti's son, in which he wrote a book called ""Translating the Dragon at the doors of the correct Bukhari"", and Imam Badruddin ebn jamaa son in his book called: ""Occasions of the Steam Tram."" Their catalog of events was to match “true Bukhari,” to illustrate how the conversation matched translation, and they attempted to provide a brief comparison of the books, and to illustrate the most important points of agreement and difference between the two Imams in explaining and guiding the “true Bukhari.”
مذكرة ماستر تخصص الحديث وعلومه
Keywords: تراجم، صحيح البخاري ، جماعة، دراسة مقارنة; Translations, Sahih Al-Bukhari, Collective, a comparative study